VILE PORNOGRAPHY, SEXUAL MISCREANTS, AND ELECTRONIC STALKERS – POLICY DISCOURSES OF YOUTH INTERNET SAFETY - Fisk, Nathan (AoIR Selected Papers of Internet Research, 2015)
Across the generations of youth who have had access to information technologies, prevalent media and legislative discourses have taken as their object the protection of children as they go about playing, communicating and working online. As Thomas (1998) asks, “If the goal of law enforcement is to ’protect’ us from high tech hoodlums, as is so often claimed, the question remains: what is it that is being ’protected’? And what does it mean to be ’protected’? What are the ’positive effects’ of protection?” (p. 386). In the case of Internet safety, legislative and media discourses have variously figured youth and information technologies relative to the future of the nation – producing and reconstituting spaces, technologies and individuals. Cyberspaces, digital natives, floods of vile content, and shadowy Internet predators are produced through these discourses, grounded in conceptual resources made possible by varying patterns of technology adoption and use. The protection of youth online requires an intertwining of childhood and technological development, bounding off youth from various forms of behavior, content, and predatory individuals. Legislative and media images of an information based economy of the future striate technological spaces into more efficient spheres of childhood development, producing a workforce which will in turn develop and support the information technologies of the 21st century.